Physico-chemical and Nutritional Properties of Cornelian Cherry Fruits (Cornus mas L.) Grown in Turkey - Hakki Kalyoncu, Ismail; Ersoy, Nilda; Yilmaz, Mehmet (Asian Journal of Chemistry, 2010)
In present study, several physical, chemical, pomological and nutritional properties of cornelian cherry fruits (Cornus mas L.) selected from Konya region were determined. The cornelian cherry fruit mean weight, length, width and thickness were found to be 3.130 g, 21.15 mm, 15.5 mm, 15.35 mm, respectively. The seed of fruit mean weight, length, width and thickness were found to be 0.923 g, 14.5 mm, 6.77 mm, 6.2 mm, respectively. In addition to the levels of acidity, pH, total soluble solids, ratio (solids/acidity), texture, colour, tanin, total sugar, invert sugar and ascorbic acid were determined in fruits. Values of the acidity, pH, total soluble solids, ratio (solids/acidity), texture, colour, tanin, total sugar, invert sugar and ascorbic acid were found to be 1.983 mg/100 g, 2.617, 15.600 mg/100 g, 7.883, 0.357 kg/cm2, S60O70M90, 129.503 mg/L, 8.840 mg/100 mL, 7.130 mg/100 mL, 73,007 mg/100 mL, respectively. Studied of nutritional properties K (14300.984 ppm), Ca (1560.095 ppm), Mg (715.231 ppm), P (605.558 ppm) and S (436.754 ppm) were established as major minerals of the cornelian cherry fruits. Others were determined at minor levels. The highest minerals were K and Ca followed by Mg, P and S. On the other hand, some physical properties sphericity and aspect ratio for fruit and seed of cornelian chery fruit were found to be 80.573, 72.727 and 58.830, 46.710 % respectively. True density, was found to be 1018.703 kg/m3.